Resurgence and predominance of G3P[8] human rotaviruses in north-central Bangladesh, 2018–2019. (January 2020) - Mazid, R.; Aung, M.S.; Paul, S.K.; Ahmad, F.U.; Alam, M.; Ali, M.A.; Nath, P.; Ahmed, S.; Haque, N.; Hossain, M.A.; Kobayashi, N.
Abstract: Predominance of genotype G3P[8] rotavirus was revealed for children and adults with diarrhoea in north-central Bangladesh for a 1-year period from September 2018. The G3P[8] rotaviruses were phylogenetically close to recent Indian strains, having antigenic variation in VP7 and VP4 compared with old Bangladeshi strains.